This Deleuzian century : art, activism, life - Braidotti, Rosi; Dolphijn, Rick (Faux titre ;, 2014)
Based on Deleuze's idea that philosophy is an activity that appeals to anyone who is attuned to the desire for the ethical life, the contributions in this book question how to live the ethical life today in academia, in art but above all in our multiple ecologies of belonging.